Genetic diversity and character association in different seedling pecan (Carya illinoensis) genotypes - SINGH, DINESH; KALER, RAJESH KUMAR; KUMAR, K; SHARMA, NIRMAL (The Indian Journal of Agricultural Sciences, 2014)
The extent of variability, heritability, character association, path analysis and genetic divergence with respect to nut and kernel characters in thirty six seedling pecan genotypes were studied. The analysis of variance showed substantial amount of variability for majority of traits. The estimates of PCV were higher for all the traits investigated. High heritability estimation coupled with high genetic advance was observed for nut length and kernel oil (%) but, higher genetic gain coupled with moderate to high heritability was recorded for kernel protein and shell thickness. Further nut weight had positive and significant association with nut width, shell thickness, kernel weight, kernel width and kernel length. Based on path coefficient analysis, nut length, kernel weight, kernel percentage, kernel width, kernel length and kernel protein showed positive effects towards nut weight and kernel percentage.